Herding behaviour in energy stock markets during the Global Financial Crisis, SARS, and ongoing COVID-19*. (December 2020) - Chang, Chia-Lin; McAleer, Michael; Wang, Yu-Ann
Abstract: Environmental change created worldwide interest in investing in renewable energy. Less reliance on fossil fuels would have a substantial influence on investors for alternative energy, especially renewable energy. The literature has concentrated on empirical studies of herding behaviour in finance, but not in renewable energy. This paper fills the gap by investigating herding in renewable energy, using daily closing prices in renewable and fossil fuel energy stock returns in the USA, Europe, and Asia, for March 24, 2000–May 29, 2020, which covers the Global Financial Crisis (GFC) (2007–2009), the coronavirus crises of SARS (2003). And the ongoing COVID-19 (2019–2020) pandemic. The paper shows that: (1) for low extreme oil returns, investors are more likely to display herding in the stock market; (2) for SARS and COVID-19, herding is more likely during extremely high oil returns after the GFC; and (3) herding is more likely during periods of extremely low oil returns during the coronavirus crises. These results suggest that after the GFC, investors are more sensitive to asset losses, so they will be more likely to display herding in the stock market. However, during SARS and COVID-19, investors panic so they may unwisely sell their assets. There are strong cross-sector herding spillover effects from US fossil fuel energy to renewable energy, especially before the GFC, while the US fossil fuel energy market has a significant influence on the Europe and Asia renewable energy returns during COVID-19. During SARS, which was not a pandemic, US fossil fuels only had an impact on US renewable energy returns. Highlights: Environmental change has led to investing in renewable energy as an alternative to fossil fuels. The literature has concentrated on herding behaviour in finance, but not in renewable energy, so this paper investigates herding in renewable energy for the USA, Europe, and Asia, for the period March 24, 2000–May 29, 2020 that covers the GFC, SARS, and COVID-19. For (1) low extreme oil returns, herding is more likely in the stock market; (2) SARS and COVID-19, herding is more likely during extremely high oil returns after the GFC; and (3) extremely low oil returns during SARS and COVID-19, herding is more likely. After the GFC, investors are more likely to display herding in the stock market but, during SARS and COVID-19, investors may unwisely sell their assets. There are strong cross-sector herding spillover effects from US fossil fuel energy to renewable energy, especially before the GFC.